2016
DOI: 10.1097/01.bot.0000489982.40329.52
|View full text |Cite
|
Sign up to set email alerts
|

9. Effects of Low-Intensity Pulsed Ultrasound (LIPUS) on Osteoclasts and Osteoblasts: Analysis Using an Assay System With Fish Scale as a Model of Bone

Abstract: At 3 hours of incubation after LIPUS treatment, osteoclastic marker expression decreased while osteoblastic markers increased. Using GeneChip analysis of zebrafish scales treated by LIPUS, we found that cell death-related genes were up-regulated by LIPUS treatment. TUNEL staining showed that the number of apoptotic osteoclasts in goldfish scales was elevated by treatment with LIPUS at 3 hours of incubation. Thus, we conclude that LIPUS promotes apoptosis in osteoclasts shortly after exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…75 In addition, LIPUS could stimulate programmed cell death in osteoclasts, such as the higher number of apoptotic osteoclasts in goldfish scales representing apoptosis. 75 Moreover, LIPUS can inhibit osteoclast activity by increasing OPG and RANKL expression in osteoblasts. 76 Meng et al showed that LIPUS treatment suppressed RANKL-induced osteoclast differentiation through ERK signaling.ERK and downstream components of the c-Fos/NFATc1 cascade, such as TRAP, CTSK, ERK1/2, extracellular signal-regulated kinase 1/2; CCN2, cellular communication network factor 2.…”
Section: Osteoclastsmentioning
confidence: 99%
See 2 more Smart Citations
“…75 In addition, LIPUS could stimulate programmed cell death in osteoclasts, such as the higher number of apoptotic osteoclasts in goldfish scales representing apoptosis. 75 Moreover, LIPUS can inhibit osteoclast activity by increasing OPG and RANKL expression in osteoblasts. 76 Meng et al showed that LIPUS treatment suppressed RANKL-induced osteoclast differentiation through ERK signaling.ERK and downstream components of the c-Fos/NFATc1 cascade, such as TRAP, CTSK, ERK1/2, extracellular signal-regulated kinase 1/2; CCN2, cellular communication network factor 2.…”
Section: Osteoclastsmentioning
confidence: 99%
“…Osteoclasts partake in bone resorption, and LIPUS has been recently reported to rectify osteoclastic activities in fracture healing. Nobuo Suzuki et al using zebrafish and goldfish scales found that LIPUS could decrease the expression of osteoclastic markers while increasing osteoblastic markers 75 . In addition, LIPUS could stimulate programmed cell death in osteoclasts, such as the higher number of apoptotic osteoclasts in goldfish scales representing apoptosis 75 .…”
Section: Mechanism Of Lipus On Fracture Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical trials have demonstrated the potential of LIPUS in the field of bone tissue repair and regeneration. LIPUS not only acts on osteoblasts [ 8 ], osteoclasts [ 9 ] and mesenchymal stem cells [ 10 ] to exert osteogenic effects, but also has a positive effect on bone healing and regeneration through its effects on blood vessels and nerves [ 11 , 12 ]. Ultrasonic lipid microbubbles (MBs) can burst to form acoustic cavitation under the action of ultrasound, and the energy released can start or promote the sonochemical reaction [ 13 ].…”
Section: Introductionmentioning
confidence: 99%